2018
DOI: 10.1186/s12906-017-2075-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of Clitoria ternatea flower beverage on glycemic response and antioxidant capacity in healthy subjects: a randomized crossover trial

Abstract: Background: Clitoria ternatea L., a natural food-colorant containing anthocyanin, demonstrated antioxidant and antihyperglycemic activity. The aim of this study was to determine the effects of Clitoria ternatea flower extract (CTE) on postprandial plasma glycemia response and antioxidant status in healthy men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 50 publications
(55 reference statements)
1
41
1
9
Order By: Relevance
“…The plasma thiol level was expressed as µM L-cysteine equivalent. The level of plasma malondialdehyde (MDA) was determined according to a previously described report [10]. Plasma MDA was quantified using a method based on the formation of thiobarbituric acid reactive substances (TBARS).…”
Section: Antioxidant and Oxidant Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma thiol level was expressed as µM L-cysteine equivalent. The level of plasma malondialdehyde (MDA) was determined according to a previously described report [10]. Plasma MDA was quantified using a method based on the formation of thiobarbituric acid reactive substances (TBARS).…”
Section: Antioxidant and Oxidant Measuresmentioning
confidence: 99%
“…Moreover, a study of Jokioja et al demonstrated that consumption of anthocyanin-enriched purple potato reduced postprandial glycemia and insulinemia in healthy male volunteers when compared to the group who consumed yellow potato [9]. Chusak et al reported that acute ingestion of an anthocyanin-rich Clitoria ternatea beverage attenuated postprandial glucose together with improvement of plasma antioxidant capacity when consumed with sucrose [10]. In this regard, plant-based anthocyanins may be considered as a natural ingredient for suppression of postprandial glucose and protection of postprandial oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Efek hipoglikemia ekstrak bunga telang telah dibuktikan melalui beberapa penelitian Rajamanickam et al, 2015;Chusak et al, 2018). Pemberian ekstrak air bunga telang secara oral (400 mg/kg berat badan) kepada tikus percobaan menurunkan glukosa serum dan glikosilasi hemoglobin, serta meningkatkan insulin serum, glikogen otot hati dan tulang .…”
Section: Antidiabetesunclassified
“…Penelitian Chusak et al (2018) menunjukkan bahwa bunga telang dapat diolah menjadi minuman pengatur gula darah melalui proses yang relatif sederhana, yakni dengan maserasi atau perendaman dalam air sehingga mencapai kepekatan yang setara dengan 2,16 mg delfinidin 3-glukosida per sajian. Konsentrasi ini dapat diperoleh dengan merendam 10 hingga 15 helai bunga telang di dalam 250 ml air panas selama 15 hingga 30 menit.…”
Section: Pengontrol Gula Darahunclassified
“…Plasmakonzentrationen von Glukose und Insulin waren nach Einnahme eines zuckerhaltigen Getränks mit 1 bzw. 2 g Extrakt von Clitoria ternatea vermindert und Parameter für die antioxidative Kapazität erhöht [3]. Verwendet wurde das getrocknete Filtrat einer wässrigen Abkochung der Blüten.…”
Section: Stand Der Forschungunclassified